Pengaruh Penambahan Superplasticizer Dan Abu Batu Sebagai Filler Untuk Meningkatkan Kuat Tekan Beton Normal - Chairani Sabrina Mecha; Tri Mulyono; Prihantono Prihantono (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2018)
The purpose of this research is to determine the Superplasticizer Sikament LN as a added of cement in compressive strength test in an effort to determine the maximum compressive strength of the concrete. This research was partially adding cement with Superplasticizer with a variety of percentages 0%, 0,5%, 1%, 1,5%, and 2% of the total weight of cement. Concrete design f’c 35 MPa, W/C 0.4, 12±2 cm slump, amount of sample was 30 (3 samples for each variation for concrete life of 7 and 28 days). The results showed that 0,5% variation of Superplasticizer reached the average concrete compressive strength is 43,5 MPa; 1% variation of Superplasticizer is 42,56 MPa; 1,5% variation of Superplasticizer is 40,86 MPa and 2% variation of Superplasticizer is 40,2 MPa. The maximum concrete compressive strength contained 0,5% variation of Superplasticizer.